y = ∫ − 1 x t 2 + 4 t 2 d t − ∫ 3 x t 2 + 4 t 2 d t If y = f ( x ) , then find f ′ ( x ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
But still wondering: what is the primitive of t 2 + 4 t 2 ?
Log in to reply
∫ t 2 + 4 t 2 d t = ∫ 1 + ( 2 t ) 2 ( 2 t ) 2 d t = 2 ∫ 1 + u 2 u 2 d u = 2 ∫ tan 2 θ d θ = 2 ∫ ( sec 2 θ − 1 ) d θ = 2 ( tan θ − θ ) + C = 2 ( u − arctan ( u ) ) + C = 2 [ 2 t − arctan ( 2 t ) ] + C = t − 2 arctan ( 2 t ) + C where u = 2 t ⟹ 2 d t = d u where θ = arctan ( u ) ⟹ u = tan θ ⟹ d u = sec 2 θ d θ
Log in to reply
Tnx. I knew it was a trigonometric function, but didn't know which 1 . by heart anymore.
it's t-2arctan(t/2)
Problem Loading...
Note Loading...
Set Loading...
y = ∫ − 1 x t 2 + 4 t 2 d t − ∫ 3 x t 2 + 4 t 2 d t = ∫ − 1 3 t 2 + 4 t 2 d t = c where c is a constant.
⟹ f ( x ) f ′ ( x ) = c = 0